Prevalence and risk factors of type 2 diabetes mellitus in a rural and an urban Nigerian community: Are the demographics changing? - Ubani BC; Nkpozi MO; Ekrikpo UE; Ekuma I; Young EE; Unachukwu CN (Global Journal of Medicine and Public Health)
Background